Pengaruh pola asuh orang tua, pengetahuan agamadan keteladanan guru terhadap kualitas karakter siswa SMP Negeri 3 Sewon Kabupaten Bantul tahun pelajaran 2013/2014 - Purwanto Purwanto; Supriyoko Supriyoko (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The effect of Parent’s care, Religion knowledge, and Teacher’s Figure to the Quality of Student’s Characteristic in SMP N 3 Sewon, Bantul in the Academic year of 2013/2014. Tesis. Yogyakarta: the Graduate Program, Sarjanawiyata Tamansiswa University of Yogyakarta. This research was aimed to know the effect of parent’s care, religion knowledge and teacher’s figure that wanted to improve the quality of student’s characteristic in SMP N 3 Sewon, Bantul in the Academic year of 2013/2014. The subject of this research was class IX, SMP N 3 Sewon, Bantul in the Academic year 2013/2014 that consist of 109 students. The sample was 84 students that were taken by proportional technique. The sample sum was decided by using sample decision table from Issac and Michael. The data collection used random sampling, questionnaire. It was tested by students of class IX in SMP N 3 Sewon. The first hypothesis test used double regression analysis, the second   hypothesis to forth hypothesis used partial correlation analysis. The result of this research show that (1) it can be found the positive effect that was significant parent’s care, religion knowledge and teacher’s figure to the quality of student’s characteristic in SMP N 3 Sewon, Bantul in the academic year of 2013/2014, if parent’s care, religious knowledge, and teachers' figure is hight so th quality of student’s characteristic is hight (2) it can be found the positive effect that is significant parent’s care to the quality of student’s characterictic in SMP N 3 Sewon, Bantul in the academic year of 2013/2014, if parent’s care is hight so the quality of student’s characteristic is hight, (3) it can be found the positive effect that is significant , religion knowledge to the quality of student’s characterisic in SMP N 3 Sewon, Bantul in the academic year of 2013/2014, if  religion knowlwdge is hight so the quality of student’s characteristic is hight,  (4) it can be found the positive effect that is significant teacher’s figure to the quality of student’s characteristic in SMP N 3 Sewon, bantul in the academic year of 2013/2014, if teacher’s figure is hight so quality of students characteristic is hight.